ChemInform Abstract: Stereospecific Hydrodehalogenation of Alkenyl Bromides: A New Approach to the Synthesis of (E)‐Alkenes. Issue 34 (26th August 2014) - Chelucci, Giorgio
Abstract A variety of (E)‐alkenes (II) and (IV) is obtained by Pd‐catalyzed hydrodebromination of bromides (I) and (III) with NaBH4 and TMEDA.